2017
DOI: 10.1038/am.2017.163
|View full text |Cite
|
Sign up to set email alerts
|

Non-dissipative internal optical filtering with solution-grown perovskite single crystals for full-colour imaging

Abstract: Herein we demonstrate that solution-grown single crystals of semiconducting methylammonium lead halide perovskites (MAPbX 3 , where MA = CH 3 NH 3 + , X = Cl − , Br − and Br/I − ) can be used as semiconductor absorbers for full-colour imaging. A one-pixel photodetector prototype was constructed by stacking three layers of blue-, green-and red-sensitive MAPbCl 3 , MAPbBr 3 and MAPb(Br/I) 3 crystals, respectively. The prototype detector was demonstrated to recognize and faithfully reproduce coloured images by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 58 publications
0
57
0
Order By: Relevance
“…Within this approach to narrowband photodetection, it is particularly noteworthy that organic and perovskite semiconductors can be used not only as photoactive materials, but also as filter materials. This is enabled by the facile tunability of their absorption properties [83,113]. A particular implementation of this strategy involves using a filter made of a broadband photodetector with absorption (and responsivity) onset at a shorter wavelength than that of the photodetector at hand (input optical filtering with stacking) [113].…”
Section: Input Optical Filteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this approach to narrowband photodetection, it is particularly noteworthy that organic and perovskite semiconductors can be used not only as photoactive materials, but also as filter materials. This is enabled by the facile tunability of their absorption properties [83,113]. A particular implementation of this strategy involves using a filter made of a broadband photodetector with absorption (and responsivity) onset at a shorter wavelength than that of the photodetector at hand (input optical filtering with stacking) [113].…”
Section: Input Optical Filteringmentioning
confidence: 99%
“…This is enabled by the facile tunability of their absorption properties [83,113]. A particular implementation of this strategy involves using a filter made of a broadband photodetector with absorption (and responsivity) onset at a shorter wavelength than that of the photodetector at hand (input optical filtering with stacking) [113]. In principle, stacking multiple broadband photodetectors along similar lines has the merit of delivering narrowband devices covering multiple adjacent spectral bands (e.g., as needed for RGB colour detection).…”
Section: Input Optical Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the isostructural Cs 4 PbBr 6 ,w hich shows narrow excitonic PL only at low temperatures and at wavelengths < 400 nm, [16] Cs 4 SnBr 6 exhibits broad-band green-yellow PL at RT from STEs (peak maximum at 540 nm, Figure 1c). Upon measuring the PL excitation (PLE) and absorption spectra it was found that Cs 4 SnBr 6 resembled am olecular material with as harp excitation peak at 340 nm yielding alarge Stokes shift of about 1.2 eV (Supporting Information, Figure S4).…”
mentioning
confidence: 99%
“…In (C 4 N 2 H 14 X) 4 SnX 6 (X = Br/I), [21] the addition of iodide red-shifts both the excitation and STE emission spectra. Similarly,t he PL of Cs 4 SnX 6 shifts to 620 nm (orange emission) at aB r:Ir atio of ca.…”
mentioning
confidence: 99%